The Effect of Unemployment and Poverty on Criminality in East Java Province in Supporting State Defense - Ajeng Alfianita Abdila; Arif Tison Situmorang; Muhammad Hidayat; Akhmad Firmansyah Buhroni; Fera Septyana; Ivan Yulivan; Yudi Sutrasna (Journal of Research in Business, Economics, and Education, 2022)
The purpose of this study is to determine the effect of unemployment and poverty on crime, especially in the province of East Java in an effort to maintain national defense. This research entirely uses secondary data obtained from BPS East Java. This study uses the analisis Ordinary Least Square (OLS) approach with Eviews. The results of this study indicate that: (1) Unemployment has a positive and significant effect on crime in East Java. (2) Poverty has a positive and significant effect on crime in East Java. (3) Unemployment and Poverty have a simultaneous or joint effect on crime in East Java. Based on the results of this study, the authors suggest to the East Java Provincial Government to make policies that are oriented towards reducing the number of unemployment and poverty in East Java Province.